The impact of the working longevity of the “silver generation” on the Kazakhstani labor market - Gazizova, M.R.; Khussainova, Zh.S.; Vechkinzova, Y.A. (KU Publ., 2021)
Object: To study the impact of demographic trends on the labor market in the context of the labor activity of the older generation in Kazakhstan and to conduct a comparative analysis of the employment indicators of older people. Methods: methods of system, dynamic and structural analysis, and correlation analysis. Findings: The results of the analysis allow us to conclude that the aging process of the population actualizes the labor activity of the older population, and determines the formation of support for stimulating the employment of older people. Conclusions: Thus, the role of the older generation in the labor market is being scaled, and therefore it is necessary to consider labor activity in retirement age as an element of the formation of the lifestyle of the older generation, where the role of labor as a factor of active longevity is given a special place. The creation of working conditions necessary for the use of working capacity is a long-term goal in ensuring active longevity and meeting the needs of older people in socially significant activities
«Күміс ұрпақтың» еңбек ұзақтығының қазақстандық еңбек нарығына əсері
Влияние трудового долголетия «серебряного поколения» на казахстанский рынок труда
Keywords: Demographic transformations; population aging; employment of older persons; labor market